Analysis of primary caregivers' knowledge concerning the cariogenic risk associated with the use of pediatric liquid medications - Florencia Cáceres-Riveros; Paula Karin-Navea; Nicolás Dufey-Portilla; Cristina Barrera-Gutierréz; Javiera Brantt-Brantt (Universidad de Concepción., 2024)
Introduction: Pediatric liquid medications (PLM) are frequently administered to children, yet their usage may contribute to the onset of dental caries. Despite its prevalence, there is a notable scarcity of scientific research regarding caregivers' knowledge of this potential cariogenic risk. Objective: This study aims to assess the knowledge of the main caregivers of children aged 5 to 12 years concerning the cariogenic potential associated with the use of PLM. Materials and Methods: A cross-sectional analytical obser-vational study involving 152 primary caregivers of children aged 5 to 12 was conducted. Data were collected on caregivers' perceptions of the cariogenic risk associated with PLMs and their consumption habits. The study also assessed oral hygiene routines and evaluated the level of information provided by healthcare professionals. Results: Research findings indicated a significant lack of awa-reness among primary caregivers regarding the cariogenic risks of PLMs, with 78.95% being unaware of these risks and 47.37% unaware of the sugars present in such medications. Additionally, a high rate of PLM consumption was observed, with 63% of caregivers using them in the last year. The study underscored a notable absence of guidance from healthcare professionals, as 91.45% of the caregivers stated that they had not received instructions on tooth brushing after the administration of the PLM. Conclusions: The study highlights a significant lack of awa-reness among primary caregivers regarding the cariogenic risks associated with the ingestion of pediatric liquid medications. This deficit in information and preventive measures presents a substantial obstacle to children's oral health. To address this issue, it is crucial for healthcare professionals to offer comprehensive guidance and promote preventive measures.